(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the level of validity, practicality, and effectiveness of the Edpuzzle interactive learning media based on Problem-Based Learning (PBL) on problem-solving skills in statistics material. The research method used in this study is the research and development method. The subjects in this study were divided into two, namely development subjects and product trial subjects. The data collection tools used in this study were validation sheets, questionnaires, and tests. The resulting data was analysed descriptively quantitatively. Based on the research results that have been conducted, it can be concluded that the Edpuzzle interactive learning media based on PBL on problem-solving skills is very valid, very practical, and very effective to be used as a learning medium.